2019
DOI: 10.3389/fenvs.2019.00112
|View full text |Cite
|
Sign up to set email alerts
|

Significant Increase in Nutrient Stocks Following Phragmites australis Invasion of Freshwater Meadow Marsh but Not of Cattail Marsh

Abstract: Invasive species are a threat to biodiversity and can cause ecological degradation, however, well-established invasive species may serve valuable ecological functions. For example, in the Laurentian Great Lakes, where nutrient pollution is a major issue, highly productive Phragmites australis (European Common Reed) may provide a nutrient retention service. Yet there is a lack of research comparing carbon and macronutrient stocks in P. australis with resident plant communities, such as cattail and meadow marsh.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…and Canada Bluejoint grass ( Calamagrostis canadensis ) dominate, creating dense tufts of shorter (ca. 1 m) vegetation with greater floristic diversity, light penetration (Robichaud and Rooney 2021) and distinct litter composition (Yuckin and Rooney 2019), When P. australis invades, it displaces both cattail marsh and this shallower meadow marsh zone, as well as the at intermediate water depths, The result is a loss of vegetation diversity, structural complexity and habitat heterogeneity with consequences for avian habitat value. The greater habitat heterogeneity of remnant marsh supports greater taxonomic turnover in the bird community, providing opportunities for numerous bird species to partition resource use within distinct habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Canada Bluejoint grass ( Calamagrostis canadensis ) dominate, creating dense tufts of shorter (ca. 1 m) vegetation with greater floristic diversity, light penetration (Robichaud and Rooney 2021) and distinct litter composition (Yuckin and Rooney 2019), When P. australis invades, it displaces both cattail marsh and this shallower meadow marsh zone, as well as the at intermediate water depths, The result is a loss of vegetation diversity, structural complexity and habitat heterogeneity with consequences for avian habitat value. The greater habitat heterogeneity of remnant marsh supports greater taxonomic turnover in the bird community, providing opportunities for numerous bird species to partition resource use within distinct habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Wilcox et al 2003, Robichaud and Rooney 2021), fill in open-water pools (Able and Hagan 2013), and alter wetland hydrology (Weinstein and Balletto 1999). For example, we observed that P. australis -invaded marsh exhibits less seasonal drawdown than uninvaded areas (Yuckin and Rooney 2019). While native marsh vegetation communities are restricted by environmental conditions, such as water depth and inundation period, P. australis can establish populations across a wide moisture gradient (Packer et al 2017) and spans the entire water depth gradient occupied by resident wetland vegetation (Wilcox et al 2003, Robichaud and Rooney 2021).…”
Section: Introductionmentioning
confidence: 98%
“…This project was the first large-scale (over 1165 ha treated) use of glyphosate to control invasive P. australis in standing water in Canada. Due to the unprecedented scale and the Emergency Registration required to enable the control project, our research team designed and implemented extensive monitoring to evaluate the fate and potential effects of the herbicide (MNRF, 2018;Yuckin and Rooney, 2019;Robichaud and Rooney, in prep;Polowyk and Rooney, in prep).…”
Section: Introductionmentioning
confidence: 99%
“…However, invasive wetland plants can affect the carbon budget through several pathways. Invasive plants can directly in uence carbon cycling, for example, if they are more productive than the species they displace (e.g., Lei et al 2019), or if they produce more nutrient-rich litter (e.g., Yuckin and Rooney 2019). They can also affect carbon cycling indirectly, by altering key environmental factors in the regulation of decomposition rates, such as light penetration, oxygen availability, or water levels (e.g., Robichaud and Rooney 2021).…”
Section: Introductionmentioning
confidence: 99%